Voicing as an Essential Problem of Communication: Language and Education of Chinese Immigrant Children in Globalization. (5th June 2013) - Dong, Jie; Dong, Yan
<x xml:space="preserve">Abstract</x> This article explores voicing processes of identity construction among labor immigrants both inside China and in the Dutch Chinese Diaspora. We provide ethnographically grounded data oriented toward a theoretical point: voicing is an essential problem in communication. Whether one is able to achieve his voice—an outcome of a communicative process—is often conditioned by pretextual factors that exist before and beyond communication, and has to be negotiated in the communicative process.